2005
DOI: 10.1029/2004jd005475
|View full text |Cite
|
Sign up to set email alerts
|

A parameterization of ion‐induced nucleation of sulphuric acid and water for atmospheric conditions

Abstract: [1] This paper describes a five-dimensional parameterization of ion-induced nucleation (IIN) that covers the complete range of conditions relevant to the lower atmosphere. The parameters are (1) temperature T (190-300 K), (2) relative humidity RH (0.05-0.95), (3) number concentration of H 2 SO 4 (10 5 -10 8 cm À3 ), (4) first-order loss of H 2 SO 4 to particles (0.00009-0.0245 s À1 ), and (5) ion source rate (2-50 ion pairs cm À3 s À1 ). The parameterization is based on a steady state version of the kinetic ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 16 publications
0
63
0
Order By: Relevance
“…However, in order for neutral nucleation to be initiated for the conditions considered here, the stabilizing effect of these unidentified species should be at least as strong as that of an ion core. Quantum calculations of the bonding energies of hydrated H 2 SO 4 monomers and dimers with ammonia and several common organic compounds (Nadykto and Yu, 2006) suggest that, while such species may enhance the overall stability of hydrated H 2 SO 4 dimers, the increase in stability is far less than that associated with an ion core. Accordingly, the substances commonly assumed in ternary homogeneous nucleation (THN) theories appear to be ineffective in initiating neutral nucleation under the circumstances of these case studies.…”
Section: Time Series Of the Concentrations Of Freshly Nucleated Partimentioning
confidence: 99%
“…However, in order for neutral nucleation to be initiated for the conditions considered here, the stabilizing effect of these unidentified species should be at least as strong as that of an ion core. Quantum calculations of the bonding energies of hydrated H 2 SO 4 monomers and dimers with ammonia and several common organic compounds (Nadykto and Yu, 2006) suggest that, while such species may enhance the overall stability of hydrated H 2 SO 4 dimers, the increase in stability is far less than that associated with an ion core. Accordingly, the substances commonly assumed in ternary homogeneous nucleation (THN) theories appear to be ineffective in initiating neutral nucleation under the circumstances of these case studies.…”
Section: Time Series Of the Concentrations Of Freshly Nucleated Partimentioning
confidence: 99%
“…Depending on the nucleation mechanism or model of the nucleation mechanism, the predicted nucleation rates may differ by many orders of magnitude (Lucas and Akimoto, 2006;. Globally, Lucas and Akimoto (2006) showed that the maximum nucleation rates varied by five orders of magnitude between the Vehkamäki et al (2002) binary nucleation parameterization, ternary nucleation parameterization, and Modgil et al (2005) ion-induced nucleation parameterization.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of supercritical particles smaller than the smallest represented particles due to coagulation among each other and with larger aerosol is then neglected, leading to an overestimation of particle formation rates. The resulting errors add to the intrinsic errors of aerosol nucleation parameterizations, which may exceed a factor of 2 Modgil et al, 2005). Figure 4a compares nucleation rates with formation rates of particles exceeding 2.5 nm in diameter, and illustrates the errors which may arise when the aerosol nucleation rate is used in lieu of the formation rate of larger particles: The nucleation rates markedly overestimate the >2.5 nm particle formation rates, in some cases by many orders of magnitude.…”
Section: Comparison Of Different Particle Formation Ratesmentioning
confidence: 99%
“…the determination of the surface tension of small molecular clusters of a given composition, and on the vapor pressures of the involved molecules above the corresponding bulk solution. Modgil et al (2005) parameterized nucleation rates that were calculated with a numerical aerosol model that resolves the initial steps of cluster formation molecule by molecule.…”
Section: Representing Secondary Aerosol Formation In Atmospheric Modelsmentioning
confidence: 99%